الكليات الفقهية من خلال القوانين الفقهية لابن جزي - نور الهدى قديم; حدة يوسفي; د/مصطفى شطة (جامعة عمار ثليجي الاغواط, 2024)
ملخص اعتنت المدارس الفقهية الإسلامية بالتصنيف في فقه الخلاف العالي أو مايسمى بالفقه المقارن وكان للمدرسة المالكية السبق في هذا المجال ، حيث ظهر ببلاد الأندلس العالم المشارك الفقيه الأصولي المفسر المجاهد أبو القاسم محمد ابن جزي . فأضاف وأبدع بتأليفه لكتاب ــ القوانين الفقهية ــ وهو تصنيف مهم في بابه . وأهمية علم الكليات الفقهية تكمن في ضبط الفروع وجمع شتاتها وصنفوا مصنفات لكنها لم تشمل الكليات الفقهية المتناثرة في كتب أئمتهم . وعُدّ هذا الكتاب ــ القوانين الفقهية ــ من مظان تلك الكليات عندهم . وتبينّمن خلال هذا البحث الأحكام الفقهية الخاصة بباب القضاء والأبواب المشاكلة للأقضية والتي دُونت في كتاب القوانين الفقهية للإمام ابن جزي – رحمه الله – وذالك من خلال التطرق إلى كلياتها الفقهية بشرحها وبيان أدلتها الشرعية وأيضاً ذكرنا تطبيقات التي يحصل بها إيضاح الكلية الفقهية . وهذا بعد أن توضّح المعنى المراد بالكلية الفقهية ، وكذلك عُرف بالإمام ابن جزي وكتابه القوانين الفقهية مصدر تلك الكليات . Summary: Islamic jurisprudential schools have focused on classification within high-level jurisprudence, also known as comparative jurisprudence. The Maliki school led in this field, particularly with the emergence of IbnJuzayy. He made significant contributions by composing the book "Jurisprudential laws", which is a pivotal work in this area. The importance of the science of comprehensive jurisprudential principles lies in organizing branches of law and consolidating their scattered aspects. While scholars authored compilations, these did not encompass all scattered jurisprudential principles found in their imams' books. "Jurisprudential laws" was considered a principal source of these principles among them. This research reveals the specific jurisprudential rulings related to judicial matters and contentious issues faced by courts, as documented in IbnJuzayy's Jurisprudential laws". It examines these jurisprudential principles by explaining them, clarifying their legal evidence, and discussing practical applications that elucidate their jurisprudential significance. This clarification follows an explanation of the intended meaning of jurisprudential principles. Imam IbnJuzayy and his book "Jurisprudential laws" are recognized as sources for these jurisprudential principles.
باب القضاء انموذجا - دراسة فقهية -